Bleb-related tuberculous endophthalmitis following combined phacoemulsification and trabeculectomy with mitomycin C. Issue 3 (24th March 2020) - Seth, Praveen Kumar; Sharma, Savitri; Senthil, Sirisha
Abstract : A one-eyed 67-year-old man with 20/400 vision, dense cataract, previously failed trabeculectomy and medically uncontrolled advanced glaucoma underwent a single-site phacoemulsification with repeat trabeculectomy and mitomycin C. One-week postoperatively, vision in the right eye improved to 20/120, good bleb and intraocular pressure (IOP) of 14 mm Hg. By third postoperative week, patient presented to the emergency with diminished vision, pain and redness in right eye of 2 days duration and was diagnosed to have bleb-related endophthalmitis (BRE). Vitreous biopsy, smear from the bleb were taken and underwent pars plana vitrectomy with intraocular antibiotic injection. Smears and cultures were negative however, aqueous DNA-PCR was positive for Mycobacterium tuberculosis . Revisited history revealed treated pulmonary tuberculosis 3 years ago with a positive Mantoux test (17 mm) and hilar prominence on chest X-ray. One month after starting anti-tubercular therapy (ATT), the BRE resolved and vision improved to 20/60 with IOP of 14 mm Hg and the ATT was continued.